PENGOMPOSAN LIMBAH TEH HITAM DENGAN PENAMBAHAN KOTORAN KAMBING PADA VARIASI YANG BERBEDA DENGAN MENGGUNAKAN STARTER EM4 (EFECTIVE MICROORGANISM-4) - Syafrudin Syafrudin; Badrus Zaman (TEKNIK, 2007)
Black tea waste composting needs dryer material to absorb moisture of waste which is to be left. Dryermaterial used is goat manure. To make faster composting proccess and decrease rot smell potency which isout from heap, so used Effective Microorganism 4 (EM4). This research have direction to know characteristicof mature compost, the optimal comparison of mixing composition black tea waste and goat manure withEM4 addition, and cost needed to make compost. Variations taken are control variation (black tea waste), Avariation (black tea waste + 30 ml EM4), and B variation (black tea waste : goat manure + 30 ml EM4). Bvariations include B1 variation (1 : 1), B2 variation (3 : 2), B3 variation (7 : 6), and B4 variation (7 : 8). Theresult of this research shown most optimal composting is B3 variation with content of Organiccarbon:Nitrogen:Phospor:Kalium: C/N ratio: water content is 12,411% :1,063% :0,581 %:K 1,608%:11,68: 46,464 .